Cognitive and Web Phenotypes of the Western Black Widow Spider - (:unkn) unknown (My University, 2022)
Animals with brains create mental representations of their environment and their own position within it, and use these representations to make decisions. The information used to create mental representations, and how animals use representations to make decisions, are functions of an animal’s evolution and ecology. Mental representations can be as simple as remembering the direction and distance home, or as detailed as a human’s mental map of their own home. I used behavior assays designed to reveal the contents of mental representations to investigate how a web spider creates representation of its environment and objects within it, and uses these representations to guide decision making. Studies of how animals create internal representations have focused largely on understanding how animals with acute vision form representations based on visual information. I used western black widow spiders (Latrodectus hesperus) in my experiments, because web spiders have poor vision and rely largely on sensing vibrations transmitted through their webs. I first explored whether black widows form memories of where they capture prey on the web and whether they alter future web building behavior in response to past differences in prey capture location. I found that black widows did not adjust their web architecture in response to past prey capture experience. However, web architecture differed between spider sexes and spider families, and spider families differed in their response to past prey capture experience. I next investigated whether black widows use internal representations when navigating their webs. I used assays in which I displaced spiders on their webs and observed their attempts to return home. I found that black widows used representations—in the form of path integration vectors that contain information about a spider’s distance and direction from home—when navigating. I next directed my attention toward whether black widows direct their attention inward toward their internal representations. This ability is a defining feature of basic consciousness, and to my knowledge would be the first direct evidence of consciousness in an invertebrate. I designed a novel assay of inwardly directed attention by manipulating whether a spider’s representation matched its currently occupied web or not and providing spiders with a salient prey cue that they would only ignore if they were distracted by the mismatch between internal representation and external web. Black widows did sometimes become distracted by such a mismatch, and thus possessed basic consciousness. The assay I used to detect consciousness in black widows is generalizable and could be used to test for consciousness in myriad animals. Finally, I explored whether black widows store specific information about their captured prey in memory. I used an assay of searching effort to determine whether black widows remember prey capture location and relative prey size. Black widows formed memories of captured prey, regardless of prey capture site. However, black widows only differed their search effort in response to changes in relative prey size when they had captured prey on the floor of their enclosure. This could indicate that either black widows only formed memories of prey size after capturing prey on the floor or that black widows only used the remembered prey size to make decisions after capturing prey on the floor, but the assay I used could not differentiate between the two possibilities. My behavioral assays revealed that black widows create mental representations of their web and prey, and that they possess basic consciousness. Each of my experiments considered the evolution and ecology of black widows, and demonstrated that investigations of the contents of animal minds that use behavioral assays in conjunction with knowledge about the animal’s ecology, evolution, and neurobiology are especially fruitful.
Keywords: behavioral ecology; cognition; memory; representation